Reciprocal Interactions between Cell Adhesion Molecules of the Immunoglobulin Superfamily and the Cytoskeleton in Neurons - Leshchyns'ka, Iryna; Sytnyk, Vladimir (Frontiers in Cell and Developmental Biology, 2016)
Cell adhesion molecules of the immunoglobulin superfamily (IgSF) including the neural cell adhesion molecule (NCAM) and members of the L1 family of neuronal cell adhesion molecules play important functions in the developing nervous system by regulating formation, growth and branching of neurites and establishment of the synaptic contacts between neurons. In the mature brain, members of IgSF regulate synapse composition, function and plasticity required for learning and memory. The intracellular domains of IgSF cell adhesion molecules interact with the components of the cytoskeleton including the submembrane actin-spectrin meshwork, actin microfilaments, and microtubules. In this review, we summarize current data indicating that interactions between IgSF cell adhesion molecules and the cytoskeleton are reciprocal, and that while IgSF cell adhesion molecules regulate the assembly of the cytoskeleton, the cytoskeleton plays an important role in regulation of the functions of IgSF cell adhesion molecules. Reciprocal interactions between NCAM and L1 family members and the cytoskeleton and their role in neuronal differentiation and synapse formation are discussed in detail.